The Effect of Career Development, Perception of Organizational Justice and Job Satisfaction on Teacher’s Organizational Citizenship Behavior - Naway, Forry A.; Haris, Ikhfan (International Review of Management and Marketing, 2017)
The objective of this research is to examine the effect of career development, perception of organizational justice and job satisfaction on teacher’s organizational citizenship behavior of the Public Senior High School in Gorontalo regency, Gorontalo province. This research used the quantitative approach with survey method. The samples of this research were 178 employees selected randomly. The data were obtained by distributing questionnaire and analyzed by using descriptive statistics and path analysis in inferential statistics. The results of the research can be concluded that: career development had a direct effect on teacher’s organizational citizenship behavior, perception of organizational justice had a direct effect on teacher’s organizational citizenship behavior, job satisfaction had a direct effect on teacher’s organizational citizenship behavior, career development had a direct effect on teacher’s job satisfaction, perception of organizational justice had a direct effect on teacher’s job satisfaction. Therefore to improve teacher’s organizational citizenship behavior career development, perception of organizational justice and job satisfaction should be improved. Keywords: career development, organizational justice, job satisfaction, organizational citizenship behavior JEL Classifications: D23, L2